2009
DOI: 10.3171/2009.1.spine08726
|View full text |Cite
|
Sign up to set email alerts
|

Cervical laminoplasty for the treatment of cervical degenerative myelopathy

Abstract: Object The objective of this systematic review was to use evidence-based medicine to examine the efficacy of cervical laminoplasty in the treatment of cervical spondylotic myelopathy (CSM). Methods The National Library of Medicine and Cochrane Database were queried using MeSH headings and keywords relevant to cervical laminoplasty and CSM. Abstracts were reviewed and studies meeting the inclusion criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 48 publications
2
50
0
Order By: Relevance
“…12,22,28 Although laminoplasty has advantages such as a lower incidence of postoperative cervical kyphosis and preservation of range of motion (ROM), many authors have reported a significant decrease in cervical ROM after laminoplasty despite the good postoperative neurological improvements experienced by their patients. [1][2][3][4][5][6]11,12,[15][16][17][18][20][21][22]25,26,28 However, they have investigated using only 2D flexion and extension on lateral radiographs. To our knowledge, there has been no report of 3D motion analysis about cervical laminoplasty, including coupled motion and precise intervertebral motion.…”
mentioning
confidence: 99%
“…12,22,28 Although laminoplasty has advantages such as a lower incidence of postoperative cervical kyphosis and preservation of range of motion (ROM), many authors have reported a significant decrease in cervical ROM after laminoplasty despite the good postoperative neurological improvements experienced by their patients. [1][2][3][4][5][6]11,12,[15][16][17][18][20][21][22]25,26,28 However, they have investigated using only 2D flexion and extension on lateral radiographs. To our knowledge, there has been no report of 3D motion analysis about cervical laminoplasty, including coupled motion and precise intervertebral motion.…”
mentioning
confidence: 99%
“…Therefore, some surgeons would suggest early surgery for patients with CSM to ameliorate the risk of SCI. 2,9,19,21,22,24,27,33 However, there are insufficient data to correlate CSM with SCI, and whether the risk of SCI can be altered by surgical intervention remains elusive.…”
mentioning
confidence: 99%
“…erative Disease devote 4 chapters to the surgical management of myelopathy, including specific chapters devoted to the surgical techniques of laminectomy, 23 laminoplasty, 17 laminectomy with instrumented fusion, 1 and anterior cervical decompression with instrumented fusion.…”
mentioning
confidence: 99%